Processes Involved In Construction Project Planning - Zakaria, N.; Mohammed, A.H.; Kamaruddin, T. (2009)
Project planning is essential to a construction project. It has been identified as one of the critical success factors for a construction project. However, most of the local main contractors are not equipped with the knowledge and skills related to the project planning processes. The main objective of this study is to investigate the processes involved in the preparation of construction project planning. A questionnaire survey was conducted to achieve the objectives of the study. Data analysis was performed by using the established statistical software that is Statistical Package for Social Science (SPSS). The processes involved in the preparation of construction project planning have been identified and ranked accordingly. Results show that twenty processes are involved in the preparation of construction project planning by the contractors as follows; identify client’s requirement, determine project objective, determine scope of work, determine strategic and tactic for execution the project, produce hierarchy of project’s organization for all parties involved, determine activities and prepare work breakdown structure, determine task and responsibility for each activity, identify project duration, identify sequence of activities, identify duration, identify resources, identify cost, identify early start and late finish for each activity, co-ordinate sequence of activity duration, resources, cost early start and late finish, prepare schedule of work, prepare budget, supervise and control the prepared schedule, select and supervise selected sub-contractors, prepare project summary and analyze project risk. Based on these results,project planning evaluation model will be developed and will be validated.